Development of Research Instrument for the Investigation of Students’ Prior Knowledge in Physical Education - Mastrogiannis Ιάκωβος; Antoniou Παναγιώτης; Kasimatis Αικατερίνη (Inquiries in Physical Education and Sport, 2015)
The aim of the present study was the development of a questionnaire for the investigation of 2nd grade high-school students’ preconceptions, in the context of the constructivist paradigm. The Greek Physical Education curriculum topic under consideration refers to the placement of the players in the volleyball court, when a team is defensively organized against the opponent’s offense, with single block, defensive formation with 6 in the front, team formation 4-2 and the setter in zone 3. Twenty two 14 years old students participated in the research study (10 boys and 12 girls). The results reveal indications about the validity of three research assumptions: a. Students come to class with already formed conceptions, regarding the tactics involved in the volleyball topic under examination, b. Student preconceptions were identified that differ from the generally accepted conceptions in the Physical Education scientific field of study, c. There exists commonality in the preconceptions held by the students.